Anti-seizure drugs: discovery and development - Porter, Roger (Henry Stewart Talks, 2013)
Seizures and epilepsy, Drugs for the symptomatic treatment of seizures, Finding new Anti-Seizure Drugs is a combination of serendipity, screening and rational approaches, Drug Development, Preclinical studies, Controlled Clinical Trials are needed to prove that an anti-seizure drug is effective